Representasi Sintaksis Operator Bahasa Melayu Berdasarkan Pendekatan Tatabahasa Peranan dan Rujukan (Jurnal Bahasa, 2011)
This article examines the nature and role of operators on aspects of Malay language syntax. Syntactic aspects of operators in Malay are examined using the theoretical framework of Role and Reference Grammar (RRG). Analysis of operators in Malay is based on the function words listed in the book Tatabahasa Dewan. This study reveals that the Malay language has seven types of operators, namely aspect, status, modality, direction, negation, evidential, and illocutionary force. Each operator has a role in the Layered Structure of the Clause (LSC), that is the operator aspect, negation and direction to modify the sentence on the nucleus level, modalities of the operator to modify the core layers, and finally, operator status, evidential and illocutionary operator also modify the clause level. By using the theoretical framework of RRG, this study demonstrates an alternative way to explain the nature and role of operators in Malay.